Realitas Pemuda Pekerja Paruh Waktu dan Ketidakpastian Risiko Masa Depan Dunia Kerja - Luly Triningsih; Nanda Harda Pratama Meiji; Seli Septiana Pratiwi; Deny Wahyu Apriadi (Faculty of Social Science, Universitas Negeri Malang, 2025)
The problems in the world of work do not only arise when someone has graduated from their education. There are many part-time job opportunities for young people, even though they are studying. The proliferation of cafes and various types of trade and service businesses in the Malang City area, one of Indonesia's educational cities, has also contributed to creating additional jobs for students. However, the context of part-time work has dynamics and is also prone to exploitative contexts when viewed from the perspective of the world of work. This study uses a qualitative research method with a phenomenological approach to explore data from informants of part-time student workers in the Malang City area. The results obtained indicate that part-time work also has future risks where there is a system that tends to be exploitative. Therefore, the dynamics of part-time work should be viewed from various perspectives, such as sociology, economics, youth studies, and even law, to reduce potential risks in the future.